Cystic fibrosis: A look into the future of prenatal screening and therapy. Issue 1 (March 2015) - Nishida, Kevin; Smith, Zachary; Rana, Dane; Palmer, Jereme; Gallicano, G. Ian
Abstract : Despite recent guidelines suggesting prenatal screening for carriers of cystic fibrosis (CF) mutations, many physicians do not offer patients this service or even counseling. Some argue that the risks of miscarriage associated with prenatal diagnostic techniques outweigh the benefit of added insight, but with the advent of newer, noninvasive techniques, risks of miscarriage may be significantly lowered. Prenatal diagnosis provides parents the time to prepare for raising a child with CF, and soon, could provide treatment options in utero that could improve quality of life. Here, we describe two of the most promising gene therapy approaches: lentivirus and adenoassociated virus (AAV)‐mediated gene transduction. Thus, prenatal detection and treatment is in a most crucial stage for care of patients with CF. Birth Defects Research (Part C) 105:73–80, 2015. © 2015 Wiley Periodicals, Inc.